William Sharp and "Fiona Macleod" A Life - Halloran, William F. (Open Book Publishers, 2022)
William Sharp (1855-1905) conducted one of the most audacious literary deceptions of his or any time. A Scottish poet, novelist, biographer, and editor, he began in 1893 to write critically and commercially successful books under the name Fiona Macleod who became far more than a pseudonym. Enlisting his sister to provide the Macleod handwriting, he used the voluminous Fiona correspondence to fashion a distinctive personality for a talented, but remote and publicity-shy woman. Sometimes she was his cousin and other times his lover, and whenever suspicions arose, he vehemently denied he was Fiona. For more than a decade he duped not only the general public but such literary luminaries as George Meredith, Thomas Hardy, Henry James, William Butler Yeats, and E. C. Stedman. Drawing extensively on his letters, his wife Elizabeth Sharp's Memoir, and accounts by friends and associates, this biography provides a lucid and intimate account of William Sharp's life, from his rejection of the dour religion of his Scottish boyhood, his turn to spiritualism, to his role in the Scottish Celtic Revival in the mid-nineties. The biography illuminates his wide network of close male and female friendships, through which he developed advanced ideas about the place of women in society, the constraints of marriage, the fluidity of gender identity, and the complexity of the human psyche. Uniquely this biography reveals the autobiographical content of the writings of Fiona Macleod, the remarkable extent to which Sharp used the feminine pseudonym to disguise his telling and retelling the complex story of his extramarital love affair with a beautiful and brilliant woman. The biography illuminates not only the talented and conflicted William Sharp, but also the cultural landscape of Great Britain in the late-nineteenth century. From late Pre-Raphaelitism through the ""yellow nineties" and on to the excesses of the early twentieth century, Sharp dabbled in all the movements that comprised what some have called the Age of Decadence.